2014
DOI: 10.1002/jsfa.6570
|View full text |Cite
|
Sign up to set email alerts
|

Barrier, structural and mechanical properties of bovine gelatin–chitosan blend films related to biopolymer interactions

Abstract: Addition of gelatin in chitosan induced greater functional properties (mechanical, barrier) due to chemical interactions, suggesting an inter-penetrated network.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
80
0
15

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 130 publications
(106 citation statements)
references
References 72 publications
11
80
0
15
Order By: Relevance
“…Control CS had negative a * and positive b * values, indicating green and yellow tint, respectively. These results followed similar trend as previously reported (Benbettaïeb, Kurek, Bornaz, & Debeaufort, ; Srinivasa, Ramesh, & Tharanathan, ). Films with B extract were green, while in those with P, grayness was dominant.…”
Section: Resultssupporting
confidence: 92%
“…Control CS had negative a * and positive b * values, indicating green and yellow tint, respectively. These results followed similar trend as previously reported (Benbettaïeb, Kurek, Bornaz, & Debeaufort, ; Srinivasa, Ramesh, & Tharanathan, ). Films with B extract were green, while in those with P, grayness was dominant.…”
Section: Resultssupporting
confidence: 92%
“…This high TS can be explained in terms of the intramolecular bond of protein in gelatin, which is unique if it is in a pure state. Benbettaieb et al () obtained similar results and explained that pure gelatin edible films had higher mechanical strength. However, pure gelatin films were more rigid compared to chitosan added films.…”
Section: Resultsmentioning
confidence: 69%
“…It can be inferred from Figure b–d that the edible film’s mechanical properties with the same concentration can vary considerably but within a standard deviation range that is similar to previous studies reported by Hosseini et al (). This attribute is due to the unstable rheological properties of gelatin (Benbettaieb et al, ; Nurul & Sarbon, ) and chitosan (Szymanska & Winnicka, ). Fitting of TS in Figure b was obtained using a cubic fitting based on the following function:TS=0.70X1+0.30X2-0.18X1X2+0.17X1X2X2-X1…”
Section: Resultsmentioning
confidence: 99%
“…These biomaterials can also be effectively used not only for their adequate barrier properties or microbial stability but also as carriers of color, flavor and bioactive additives, whereby nutrients such as vitamins, minerals and flavonoids can be incorporated within the matrix . For this reason, one of the most important advantage of producing edible coatings and films based on fruits and vegetables is that several naturally occurring bioactive ingredients can be incorporated into the packaging system and consumed with the food, supplementing functional attributes …”
Section: Introductionmentioning
confidence: 99%